Atypical Chemokine Receptor 3 Generates Guidance Cues for CXCL12-Mediated Endothelial Cell Migration - Tobia, Chiara; Chiodelli, Paola; Barbieri, Andrea; Buraschi, Simone; Ferrari, Elena; Mitola, Stefania; Borsani, Giuseppe; Guerra, Jessica; Presta, Marco (Frontiers in Immunology, 2019)
Chemokine receptor CXCR4, its ligand stromal cell-derived factor-1 (SDF-1) and the decoy receptor atypical chemokine receptor 3 (ACKR3, also named CXCR7), are involved in the guidance of migrating cells in different anatomical districts. Here, we investigated the role of the ACKR3 zebrafish ortholog ackr3b in the vascularization process during embryonic development. Bioinformatics and functional analyses confirmed that ackr3b is a SDF-1-binding ortholog of human ACKR3. ackr3b is transcribed in the endoderm of zebrafish embryos during epiboly and is expressed in a wide range of tissues during somitogenesis, including central nervous system and somites. Between 18 somite and 26 hour-post fertilization stages, the broad somitic expression of ackr3b becomes restricted to the basal part of the somites. After ackr3b knockdown, intersomitic vessels lose the correct direction of migration and are characterized by the presence of aberrant sprouts and ectopic filopodia protrusions, showing downregulation of the tip/stalk cell marker hlx1. In addition, ackr3b morphants show significant alterations of lateral dorsal aortae formation. In keeping with a role for ackr3b in endothelial cell guidance, SDF-1 gradient generated by ACKR3 expression in CHO cell transfectants guides human endothelial cell migration in a novel in vitro cell co-culture chemotaxis assay. Our results demonstrate that ackr3b plays a non-redundant role in the guidance of sprouting endothelial cells during vascular development in zebrafish. Moreover, ACKR3 scavenging activity generates guidance cues for the directional migration of CXCR4-expressing human endothelial cells in response to SDF-1.